An integrodifferential approach to modeling, control, state estimation and optimization for heat transfer systems - Rauh, Andreas; Senkel, Luise; Aschemann, Harald; Saurin, Vasily V.; Kostin, Georgy V. (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, control-oriented modeling approaches are presented for distributed parameter systems. These systems, which are in the focus of this contribution, are assumed to be described by suitable partial differential equations. They arise naturally during the modeling of dynamic heat transfer processes.
Keywords: heat transfer; predictive control; optimal control; state and disturbance estimation; distributed parameter systems; sensitivity analysis